PEMETAAN BAHAN ORGANIK TANAH PADA SAWAH IRIGASI DAN TADAH HUJAN DI KECAMATAN TUREN, MALANG - Christanti Agustina; Mochtar Lutfi Rayes; Novalia Kusumarini; Khanza Amaladewi Sudharta (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Each land use has a different vegetation density and the litter input as a source of soil organic matter. Vegetation density index can be analyzed based on the NDVI equation using the GIS approach. This study aims to determine the effect of different land uses and NDVI on soil organic matter content and the mapping of soil organic matter content. This research was conducted from AprilÂ to August 2019 in Turen District, Malang Regency. The survey method used for collecting data in the field (36 observation points) based on differences in landform, relief, slope, land use (irrigated and rainfed rice fields), and vegetation density index classes (low, medium, high). Soil samples were taken at 0-20 cm depth and analyzed for soil organic matter content. Data interpolation using IDW was used for mapping soil organic matter. The results showed that there was a very significant effect between differences in land use and NDVI class on the content of soil organic matter (p <0.001). NDVI value gives an effect of 81.5% on soil organic matter content. The distribution of soil organic matter content is classified into 5 classes, which are very low, low, moderate, high and very high.